Eva in the spotlight - Elliott, Rebecca (New York : Branches/Scholastic, 2020)
Eva's class is putting on a play, Snowy White and the seven owlets, but Eva is a little disappointed when she is cast as the Magic Mirror (and Snowy White's understudy); the owl students are making all the sets, props, and costumes, and rehearsal is a little chaotic--but the play is going well until Snowy White hurts her leg and Eva has to fill in for real.
Ages 5-7.
Grades K-1.
Keywords: Owls -- Juvenile fiction; Children's plays -- Juvenile fiction; Elementary schools -- Juvenile fiction; Diaries -- Juvenile fiction; Snow White (Tale) -- Drama -- Juvenile fiction; Owls -- Fiction; Theater -- Fiction; Schools -- Fiction; Diaries -- Fiction